2005
DOI: 10.1038/sj.ijir.3901365
|View full text |Cite
|
Sign up to set email alerts
|

Male hypogonadism. Part II: etiology, pathophysiology, and diagnosis

Abstract: Male hypogonadism has a multifactorial etiology that includes genetic conditions, anatomic abnormalities, infection, tumor, and injury. Defects in the hypothalamic-pituitary-gonadal axis may also result from type II diabetes mellitus and treatment with a range of medications. Circulating testosterone levels have been associated with sexual function, cognitive function, and body composition. Apart from reduced levels of testosterone, clinical hallmarks of hypogonadism include absence or regression of secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
64
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 50 publications
(46 reference statements)
0
64
0
1
Order By: Relevance
“…13 Although diabetes is the most reported condition related to a high incidence of hypogonadism, many chronic illnesses are reported to be accompanied by a substantial incidence of low testosterone levels. 3,[14][15][16][17][18] Guay et al 19 have reported a prevalence of hypogonadism of 36.0% in men with ED seen in an endocrinology specialty center for sexual function and dysfunction. The majority of the men, 62.0%, had a pure organic cause for their ED, whereas 28.2% had mixed organic-psychological causes and 9.8% had pure psychological causes.…”
Section: Introductionmentioning
confidence: 99%
“…13 Although diabetes is the most reported condition related to a high incidence of hypogonadism, many chronic illnesses are reported to be accompanied by a substantial incidence of low testosterone levels. 3,[14][15][16][17][18] Guay et al 19 have reported a prevalence of hypogonadism of 36.0% in men with ED seen in an endocrinology specialty center for sexual function and dysfunction. The majority of the men, 62.0%, had a pure organic cause for their ED, whereas 28.2% had mixed organic-psychological causes and 9.8% had pure psychological causes.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10] When administered cautiously, testosterone therapy is safe and effective in mitigating the signs and symptoms of hypogonadism, 11 which include lower libido; erectile dysfunction; fatigue; decreased muscle strength, bone mineral density and body hair; increased body fat; anemia; hot flushes; and mood changes. 10,12,13 Testosterone therapy may also have beneficial effects on the lipid profile and cardiovascular system. 14 Testosterone therapy for male hypogonadism is generally safe, with possible adverse effects of benign prostatic hyperplasia, erythrocytosis, sleep apnea, gynecomastia, testicular atrophy, fluid retention and local reactions at sites of buccal, topical, subcutaneous and intramuscular administration.…”
Section: Introductionmentioning
confidence: 99%
“…IN MEN, HYPOGONADISM (i.e., reduced circulating testosterone) results in a variety of detrimental effects, including the loss of skeletal muscle mass and bone mineral density (BMD) and increased visceral adiposity (52). Testosterone replacement therapy has been proposed as a means of reducing these unfavorable changes (6).…”
mentioning
confidence: 99%